Financial Literacy and Green Investment Decisions among Gen Z in Yogyakarta - Utami, Novia (PT. EQUATOR SINAR AKADEMIA, 2025)
This study investigates the relationship between financial literacy and green investment decisions among Generation Z in Yogyakarta. As environmental sustainability awareness grows, younger generations are increasingly inclined to make investment decisions that align with green and ethical values. Using a quantitative approach, data were collected from 120 respondents through structured questionnaires. The data were analyzed using regression analysis to examine the effect of financial literacy on green investment decisions. The findings indicate that financial literacy has a significant and positive influence on Gen Z’s willingness to invest in environmentally sustainable companies. Respondents with higher financial literacy tend to make more informed and responsible green investment choices. These results highlight the importance of strengthening financial education to foster sustainable financial behavior among young investors. The study offers practical implications for policymakers, educators, and financial institutions in promoting financial literacy and green investment awareness.